Africa Digest : Trends and issues in macro environment Vol. 9 - Burger, Johan (2020)
The Africa Digest is a fortnightly e-newsletter scanning the key trends in the macro-environment and industry to promote knowledge and raise understanding of business in Africa. This issue explores: 1. Trends in Agriculture - Africa’s important agriculture sector contributes greatly to the GDP of Africa’s economies, and provides employment opportunities to a vast number of Africans. Unfortunately, Africa imports far too much food (between US$35 billion and US$41 billion annually), the average age of its farmers is above 60 years. Many of its youth depart the sector to escape what they perceive as a poverty trap. Meanwhile, due to high rates of population growth and urbanisation, food production is becoming increasingly critical. 2. Mining Trends - A number of interesting trends in the mining sector have recently emerged. Governments in Africa now realise that exporting raw commodities leaves a lot of money on the table, and are thus putting in place the polices and infrastructure required to ensure value-addition. 3. Renewable Energy Trends - In Africa, the volume of writing on the topic of renewable energy in the sub-sectors — i.e. hydro, solar, and wind, and even geo-thermal — boggles the mind. Rising equipment efficiency and the rate at which costs decline combine to make renewable energy an increasingly popular choice. 4. Sustainability Trends - Africa is actively pursuing sustainability across a wide range of innovative projects, in water management, sustainable brewing, waste-to-energy, and recycling waste. Recycling waste in various formats is a trend that moves from strength to strength. The goal is to reduce waste on the one hand, while creating value for the community on the other. This value frequently takes the form of new employment opportunities, as well as development of a physical product or service. 5. Technology Trends - Technological advances are pervasive drivers of change in most, if not all, sectors in both the macro and industry environments. They change how we do business (operating models), with whom we do business, against whom we compete, the nature of our revenue and cost models, the nature of value chains, and our value propositions, to name but a few aspects. These transformations bring about both challenges and advantages.